Two WUSCHEL‐related HOMEOBOX genes, PeWOX11a and PeWOX11b, are involved in adventitious root formation of poplar. Issue 4 (22nd June 2015) - Xu, Meng; Xie, Wenfan; Huang, Minren
Abstract : The plant‐specific WUSCHEL‐related HOMEOBOX ( WOX ) transcription factors play important roles in key developmental processes, but knowledge regarding functional characterization of WOX genes in poplar remains limited. To reveal genes and signaling pathways associated with adventitious rooting in poplar, here we isolated and characterized two WOX genes through the rapid amplification of cDNA ends (RACE), sequence aligning, expression profiling, protoplast transfection and poplar transformation. Detailed information about the sequence similarity, structural features, evolutionary relationships, expression patterns and subcellular localization of the two genes were revealed. Overexpression of either PeWOX11a or PeWOX11b not only increased the number of adventitious roots on the cuttings but also induced ectopic roots in the aerial parts of transgenic poplars. Meanwhile, their overexpression in transgenic poplars affected axillary bud and leaf development. These results suggest that PeWOX11a and PeWOX11b were involved in multiple developmental processes of poplar, especially in adventitious root formation. Our results provide new insights into the molecular mechanisms underlying adventitious root formation of poplar.